Development of functionally graded dental post based on a novel silica-coated titanium powder and hydroxyapatite / Nur Farha Abdul Halim - Nur Farha, Abdul Halim (2017)
Introduction: Biomedical-graded metallic compounds such as titanium, stainless steel, and their alloys are potential components for fabrication of load-bearing implants due to their favorable mechanical behavior. The facile chemical and surface modification of these compounds also allows alteration of various biological and physical properties according to their intended application. Purposes: The purpose of this study was to investigate the effect of surface modification of titanium (Ti) particles by a silica protective layer on the physical, chemical and mechanical properties of hydroxyapatite-titanium (HA-Ti) composites. The new type of fabrication and characterization functionally graded material (FGM) using hydroxyapatite (HA) and silica-coated titanium (STP) were also applied in this study. Methods: It is well known that the formation of phases such as TixPy and CaTiO3 at elevated temperatures results in a fragile behaviour of the material without displaying any yield stress prior to the rupture, providing a weak interface bonding in the matrix. As particular approaches to remove the fragile compounds, utilization of STP particles and incorporation of low-melting-point biocompatible additives as a sintering aid. In the first phase, Ti particles were coated by thin silica layers prior to mixing with HA to prevent the undesired reactions between HA and Ti. In the second phase, developed FGM composites were successfully applied for development of thermo-mechanically stable FGMs, suitable for fabrication of load-bearing heterogeneous implants such as dental posts. Results: The decomposition of HA and oxidation of the Ti during the sintering process occurred at 11000 C. However, the undesired interaction between HA and Ti components were minimized, causing the complete removal of calcium titanate, CaTiO3 and titanate phosphides, TixPy as well as the formation of stable calcium phosphate, CaP in the iii sintered composite. In the addition of silica, SiO2 resulted in the formation of calcium silicates (mostly CaSiO3), which this compound may exhibit less negative impact on the mechanical properties compared to CaTiO3 and TixPy. According to the Vickers’ hardness value, composites containing identical weight ratios of HA and STP exhibited a relatively high value comparable to that of HA-Ti composites with a weight ratio of 3:1. Conclusion: Surface modification of titanium particles using a silica layer could significantly improve the mechanical properties of the obtained composites by increasing their thermal stability during the sintering process. As a novel of metallic-ceramic FGMs, it allows one-step facile fabrication of functionally graded dental posts (FGDPs) without the necessity of performing costly and time consuming sintering process.